Natural gas conversion II : proceedings of the Third Natural Gas Conversion Symposium, Sydney, July 4-9, 1993 - Natural Gas Conversion Symposium 1993 : Sydney, N.S.W.); Curry-Hyde, H. E. (H. Edward); Howe, R. (Russell), 1948-; ScienceDirect eBooks (Amsterdam ; New York : Elsevier, 1994)
This Symposium provided the opportunity to review progress after more than 10 years of research and development in the field of natural gas conversion. Oxidative coupling of methane as a route to higher value fuels or feedstock was a major part of the program. The advances in understanding of reaction mechanisms and catalyst structure were discussed in a Plenary paper and in many of the contributed papers. The homogeneous gas phase chemistry involved in methane oxidation is relevant not only to oxidative coupling but also to synthesis gas and methanol production via partial oxidation. This field is reviewed in a Plenary paper and contributed papers describe developments in catalysts and technology for partial oxidation to synthesis gas and to methanol. An alternative route to synthesis gas from methane currently receiving attention is carbon dioxide reforming. This technology is reviewed in a Plenary paper and recent advances are described in contributed papers. The first detailed account of the Shell SMDS Fischer-Tropsch process for production of transport fuels from natural gas recently commercialised in Malaysia is given in this book. Papers discuss structural aspects of Fischer-Tropsch catalysts, modifications of Fischer-Tropsch catalysts to produce light olefins, and the possibilities of operating a Fischer-Tropsch process off-shore. Methanol as an intermediate in natural gas conversion continues to attract attention, and methanol synthesis and conversion are discussed in contributed papers. The possibilities of finding new uses for methane are treated in a Plenary paper and arguments for using methane as a fuel rather than a feedstock are also presented. Among the new uses of methane considered are the generation of electricity in fuel cells and the use of methane as a reductant for NOx emissions. The papers will be of interest to scientists and engineers working in the field of gas conversion, transportation fuels, primary petrochemicals and catalysis.
Front Cover; Natural Gas Conversion II; Copyright Page; Preface; Organising and Advisory Committees; Financial Support; Table of Contents; Chapter 1. "Recent Advances in the Oxidative Coupling of Methane"; Chapter 2. "The Relevance of Combustion Theory to the Homogeneous Oxiddation of Methane; Chapter 3. "Aspects of CO2 Reforming of Methane"; Chapter 4. "Conversion of Natural Gas to Transportation Fuels via the Shell Middle Distillate Synthesis Process"; Chapter 5. "New Uses of Methane"; Chapter 6. "Current Ideas and Future Prospects in Metal-Catalyzed Methane Conversion "
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Synthetic fuels -- Congresses; Natural gas -- Congresses; TECHNOLOGY & ENGINEERING -- Chemical & Biochemical; Natural gas; Synthetic fuels; Natural gas -- Production; Electronic books